Architecture that reactivates the latent potential of green space in the city by intervening on the edge: a building designed for meaningful escape and connecting with your fellow man - Bitzer, Linka (University of the Free State, 2019)
Within urban machines people dwell and seek out various means of correspondence and understanding their place in the world. They are forever balancing between contrasting aspects of an urban lifestyle: the presence of order, which is manifested in the obedient essence of a city and an awareness of disarray, which is personified by the carnal need for thrill. A balance must be maintained. Too much city and the smoke of cars’ exhausts cling to your clothing in a way that becomes more suffocating than nostalgic and, even though naturalists may disagree, isolating one-self beyond the city for too long could potentially become self-inflicted exile. The danger is getting caught up in a mundane routine or losing all sense of order and purpose. A balance must be maintained. It should, however, be kept in mind that before a balance can be maintained, resources to achieve and access this balance must be available. The proposed project is a new cluster of hubs where various meet and greet events take place daily, weekly and monthly. These events introduce opportunities for meaningful meetings between business-oriented citizens as well as nomads and seekers that pass through the urban fabric. The aim of this project is to create opportunities for the city dwellers to gather on the edge of the concrete jungle, escaping the routine of conforming to the nine-to-five race, to the green King's Park. This also allows city dwellers of Westdene and the CBD to reconnect with their fellow man. The proposed program will function as a meeting arena, creating opportunities to gather in formal- or informal settings. This project is specifically focused on blurring and blending the boundary between ritual and deviation from the expected on a daily basis. The architectural intervention will serve as the mediator between these outlines on a theoretical - as well as a physical basis; the building itself is nestled in the midst of city-scape and green scape, between order and chaos. The character is hence intrinsically porous; allowing dwellers to roam freely through a permeable threshold. The interest in this project is manifested in the celebration of how people interact with one another. The conversations people have leave a patina behind on one another, and on the spaces they inhabit. This palimpsest of interactions inhabit the potential of changing how the urban fabric feels through the mark that it leaves, how it envelopes the people of the city scape. Understanding that people need to interact with one another and will seek each other out to fulfil this need is the key to unlocking the green-space of Kings Park. People need to escape the mundane routine of career-centred lives. Meeting, greeting and eating fulfils these needs. This research further investigates the celebration of the curiosity of the exceptional within each person and how architecture as an intervention between the routine and the subliminal can appease the need for urban adventures.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2019
Keywords: Place in the world, Balance; City space vs. green space; Social interaction